Cover Picture: Dibromohydantoin: A Convenient Brominating Reagent for 1, 4, 5, 8‐Naphthalenetetracarboxylic Dianhydride (Asian J. Org. Chem. 9/2013). Issue 9 (12th September 2013) - Sasikumar, M.; Suseela, Y. V.; Govindaraju, T.
<x xml:space="preserve">Abstract</x> Naphthalene diimides (NDIs) play an important role in biomedicine, organic electronics, and materials science. Large‐scale preparation of brominated 1, 4, 5, 8‐naphthalenetetracarboxylic dianhydrides (NDAs) for research on core‐substituted NDIs demands an efficient and convenient method for rapid and regioselective bromination of NDAs. In their Full Paper on page 779 ff., T. Govindaraju and co‐workers report that dibromohydantoin is an efficient and economical reagent for the bromination of NDA under mild conditions. The utility of bromo‐NDAs is demonstrated by converting them into substituted NDIs, which have tunable electronic and optical properties.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>